A bio-inspired, one-step but versatile coating onto various substrates with strong antibacterial and enhanced osteogenesis. Issue 14 (28th January 2019) - Yang, Shuoshuo; Xu, Yongpeng; Lin, Quankui; Bai, Yu; Zan, Xingjie; Ye, Qingsong
Abstract : Inspired by mussels, we reported a one-step but versatile method to fabricate a biocompatible and antibacterial coating. Abstract : It is of great interest to prepare osteogenic and antibacterial coatings for successful implants. Current coating techniques suffer from being time-consuming, substrate material or shape dependence, expensive equipment, environmental pollution, low stability, processes that are difficult to control, etc. Herein, inspired by mussels, we report a one-step and versatile method to fabricate a dual functional coating. The coating is finished in minutes independently of materials or dimensions of substrates. Thus, our coatings exhibit strong antibacterial ability against both Gram-positive bacteria S. aureus, and Gram-negative bacteria E. coli, support the proliferation of dental pulp stem cells (DPSCs), and are powerful for inducing osteogenic differentiation. The universality, facility, rapidness, and mildness of our coating process, which is also environmentally-friendly and cost-effective, points towards potential applications in bone or dental implants.